The Relationship Between Musculoskeletal Injuries and Stress Load in Emergency Medical Staff of Hamadan Province in 2019 - Mohamad Mehdi Sahraei; Mehdi Molavi Verdanjani; Alireza Soltanian; Mahnaz Khatiban (Hamadan University of Medical Sciences, 2021)
Purpose and Importance of Research: Emergency medical staff who are at the forefront of health care delivery face many occupational stresses that have psychological, physical, behavioral, and organizational consequences for them, including musculoskeletal disorders. The purpose of this study was to investigate the correlation between musculoskeletal injuries and stress load tolerance among medical emergency staffs in Hamedan province. Materials and Method: In this descriptive-correlational study, conducted in 2019, 76 (40%) of urban and 114 (60%) of employees of road bases were selected from among emergency medical staff of Hamadan, Iran. Data were collected using Nordic Musculoskeletal Injury Questionnaire and Occupational Stress Questionnaire. Data were analyzed by SPSS 23 using descriptive statistics, t-test and Spearman correlation coefficient. Results: The mean age of the participants was 34.05 (± 8.11) years and the work experience was 123.42 (±84.22) months. The majority (77%) were married, 57.3% had undergraduate degrees and 46.9% had formal employment. Employee stress burden was 503.3 (161.23%) out of 1050 points. Persons who had musculoskeletal disorder due to their job had reported more stress than others; hoever, this difference was not significant (P<0.05). People with musculoskeletal disorders in neck reported higher stress load (P<0.05) than others which was not significant. There was a significant relationship between type of employment, work experience, and type of exercise with musculoskeletal disorders (P<0.05). Conclusion: There was a significant relationship only between stress and musculoskeletal damage. By modifying and eliminating stressors in emergency personnel's routines, by holding workshops on ergonomic principles as well as stress reduction principles, it is possible to reduce the physical disorders of emergency personnel.